ANALISIS JARINGAN KLUB DAN PEMAIN SEPAK BOLA BUNDESLIGA JERMAN MENGGUNAKAN METODE SOCIAL NETWORK ANALYSIS - Firdaus, Muhammad Romy; Maulana, Michael Wahab; Atmiati, Mina; Anggriana, Maria; Baptista, Stella Maris Juhar (Program Studi Pendidikan Manajemen Perkantoran, 2021)
AbstractThis study aims to determine and analyze the network formed between clubs and players data in the Bundesliga from 2015 to 2020. The purpose is to find out the key player in term of the club with the most number in player transfers and player updates, as well as the most active players or players who changed club the most in the last five years in the Bundesliga. Scrapping method is used for data retrieval while social network analysis is used for data analysis so that the key players from the Bundesliga network in the last five years can be found in the network and the